Lanthanum chloride precipitation-based toxicoproteomic analysis of 3-monochloropropane-1,2-diol toxicity in rat kidney reveals involvement of extracellular signal-regulated kinase 2 - Oberemm, Axel; Braun, Monique; Sawada, Stefanie; Pink, Mario; Frenzel, Falko; Rozycki, Christel; Meckert, Christine; Zabinsky, Elke; Braeuning, Albert; Lampen, Alfonso (Archives of Toxicology, 2017)
The heat-induced food contaminant 3-monochloropropane-1,2-diol (3-MCPD) and its fatty acid esters exert nephrotoxicity in rodents. Previous studies including a non-targeted toxicoproteomics approach using samples from a 28-day oral toxicity study in rats with 10 mg/kg body weight (b.w.) of 3-MCPD, an equimolar dose of 53 mg/kg b.w. 3-MCPD dipalmitate and a lower dose of 13.3 mg/kg b.w. of 3-MCPD dipalmitate, revealed substance-induced alterations in metabolic pathways, especially for glycolysis and energy metabolism. In order to obtain deeper insight into mechanisms of 3-MCPD toxicity, samples from the above-mentioned study were reanalyzed using a lanthanum chloride precipitation-based toxicoproteomics approach in order to increase the yield of phosphorylated proteins, crucial players in cellular signaling. A comparison of standard 2D-gel-based proteomics and lanthanum chloride precipitation was performed, thus providing a comprehensive case study on these two methods using in vivo effects of an important food toxicant in a primary target organ. While resulting in similar 2D-gel electrophoresis pherograms and spot counts, data analysis demonstrated that lanthanum precipitation yielded more significantly deregulated proteins thus considerably improving our knowledge on 3-MCPD-dependent proteomic alterations in the kidney. 3-MCPD-induced deregulation of the phosphorylated, active version of extracellular signal-regulated kinase 2 (ERK2) in rat kidney was demonstrated using mass spectrometry and immunohistochemistry. In summary, this paper for the first time links 3-MCPD effects to deregulation of the ERK/mitogen-activated protein kinase signaling pathway in rat kidney and demonstrates that lanthanum chloride precipitation is suited to support the gain of mechanistic knowledge on organ toxicity using 2D-gel-based proteomics.
EVALuna2:9761